Prophylactic Effect of Ethanolic Extract of Saussurea Costus Roots Against Hepato- Renal Toxicity Induced by Diazinon in Chickens - Hamad, Alaa K.; Kadhem, Mariam (مجلة الانبار للعلوم البيطرية)
The study was performed to investigate the prophylactic role of Saussurea costus roots in the functional and histological changes caused by diazinon in the liver and kidneysin chickens. 18 chickens were used of Arbor Acres strain at 54 days of age and 1300-1500 gm average of body weight was used for this purpose. The birds were divided into 3 groups equally (6chicken in each groups), Group 1: served as a control negative received distilled water 1 ml. Group 2: served as a positive control group, received diazinon at a dose of 0.2 mg/kg/day. Group 3: were given an ethanolic extractof Saussurea costus at dose 300 mg/kg, then after one hour administrated diazinon at the dose of 0.2 mg/kg/day, this group served as a prophylactic group. The doses were given orally once daily for 4 weeks.The results of group 2 showed clinical signs such as ruffled feathers, salivation, diarrhea, breathing from the mouth, teary eyes, drooping of wings. The body weights of the chickens and weights of the liver and kidneys of group 2 significantly declined (p≤ 0.05) compared with groups 1 and 3. There was a significant decrease (p≤ 0.05) in WBC count, lymphocyte, total protein, albumin, GSH, SOD, CAT, and GPX levels, while a significant increase (p≤0.05) in heterophil, ALT, AST, creatinine, urea, uric acid, and MDA compared with group 1. The gross examination of the liver and kidney of group 2 were pale, easily crumbles and smaller than that of group 1. Histopathological changes of the liver of group 2 including congested and dilated central vein, vacuolated cytoplasm of hepatocytes, focal necrotic tissue filled with inflammatory cells, thickening of the bile duct, thickening wall of the portal artery. fibroblast in portal area, dilated sinusoid. Histopathological changes of the kidney including dilatation of renal tubule, hemorrhage, and atrophy in the glomerulus. we concluded that administration of ethanolic extractof Saussurea costus resulted in amelioration of the morphological changes in diazinon treated chickens, improved parameters and restored the parameters to near normal compared with group 1. These results revealed that Saussurea costus roots acts as an antioxidant substance and has a hepatic and renoprotective effect against toxicity induced by diazinon.